SPORT DIPLOMACY AND STATE SOVEREIGNTY: CASE STUDY ON INDONESIA’S EFFORT TO GUARD THE SOVEREIGNTY OF PAPUA - Siburian, Erni Eriza; Afriansyah, Arie (Yustisia, 2018)
Various efforts are made by Indonesia to maintain sovereignty over Papua. One of the efforts taken by the Government of Indonesia is to conduct sports diplomacy through sports cooperation with Melanesian Searhead Group (MSG) member countries. MSG is one of the most intense international organizations to raise the issue of independent Papua.Through descriptive research with normative juridical approach, the authors examine the rules / legal principles relating to how the role of sports diplomacy as a public diplomacy strategy in maintaining the sovereignty of the state: a case study of Indonesia's efforts in maintaining sovereignty in Papua. Based on this, the researchers concluded that sports diplomacy is an important and effective diplomacy tool in maintaining the sovereignty of the state and can create good image of a country where sports can be used as a tool to show togetherness and bring people closer from different background without being associated with differences in race, skin color, religion, or characteristics.